Między odpowiedzialnością a sumieniem. Wyzwania etyczne zawodu coacha jako profesji o charakterze rozwojowo-pomocowym = Between responsibility and conscience. Ethical challenges of the coaching as a development and assistance profession - Zegzuła-Nowak, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article, the author poses a question about the essence of the profession of a coach from an ethical perspective, i.e. as a occupational activity of an aid and development nature, in line with the contemporary trend of expert activity supporting the process of human self-development. The idea behind the work of a coach is to support a person in setting specific, individualized goals and striving to achieve them in order to improve the quality of his life.
Keywords: Kodeks Etyczny Coacha; zawód rozwojowo-pomocowy; relacja coachingowa; dylemat etyczny; odpowiedzialność zawodowa; zawód zaufania publicznego; Coach`s Code of Ethics; development and assistance profession; coaching relationship; ethical dilemma; professional responsibility; profession of public trust